Development of prediction models for domestic chores resumption among mild stroke patients three months after discharge from specialized rehabilitation wards: A multi-center prospective cohort study. Issue 3 (3rd April 2023) - Kobayashi, Ryu; Kobayashi, Norikazu
ABSTRACT: Background: Whether stroke patients resume domestic chores is one of the major issues associated with their quality of life. Prediction models for domestic chores resumption among stroke survivors can be useful for setting goals and planning rehabilitation. Objectives: To develop prediction models for individual domestic chores resumption among mild stroke patients three months after discharge from specialized rehabilitation wards. Methods: Ninety-one stroke patients admitted to specialized rehabilitation wardswere included in the analyses. We assessed the prestroke and three months post-discharge frequencies of six domestic chore items of the Frenchay Activities Index. Demographics and candidate predictors such as paralysis severity, cognitive function, walking speed, and self-efficacy were collected at discharge. Binary logistic regression analyses were performed to build prediction models for individual domestic chores resumption after stroke. Results: The preparing meals model included walking speed (OR = 1.05) and cognitive function (OR = 1.29) as predictors; washing up model, walking speed (OR = 1.04); washing clothes model, walking speed (OR = 1.06), and number of family members living together (OR = 0.42); light housework model, walking speed (OR = 1.06); heavy housework model, walking speed (OR = 1.03), cognitive function (OR = 1.38), and self-efficacy (OR = 1.91); and local shopping model, walking speed (OR = 1.05), age (OR = 0.94), and number of family members living together (OR = 0.61). Conclusions: Our models may be useful in clinical practice to streamline the setting of goals and development of therapeutic strategies for individual domestic chores resumption among mild stroke patients.